Forecasting U.S. Investment - Rabanal, Pau (IMF Working Papers; Working Paper ;, 2010)
The driving force of U.S. economic growth is expected to rotate from the fiscal stimulus and inventory rebuilding in 2009 to private demand in 2010, with consumption and particularly investment expected to be important contributors to growth. The strength of U.S. investment will hence be a crucial issue for the U.S. and global recovery. On the basis of several traditional models of investment, we forecast that the U.S. investment in equipment and software will grow by about 10 percent on average over the 2010-12 period. The contribution of investment to real GDP growth will be 0.8 percentage points on average over the same period.